Iron-rich food consumption and associated factors among children aged 6-23 months in Sierra Leone: multi-level logistic regression analysis - Birhan Ewunu Semagn; Zenebe Abebe Gebreegziabher; Wondwosen Abey Abebaw (BMC, 2023)
Abstract Background Iron deficiency is the most common micronutrient deficiency worldwide. Also, iron deficiency is a significant public health problem in low- and middle-income countries. Thus, this study aimed to assess iron-rich food consumption and associated factors among children aged 6-23 months in Sierra Leone. Method This study is a cross-sectional study based on data from the Sierra Leone Demographic and Health Survey dataset with a total weighted sample of 2622 children aged 6-23 months. Data cleaning, coding, and labeling were done using STATA version 14 software. A multilevel logistic regression model was employed to identify associated factors. Result Almost half (53.38%) of children aged between 6-23 months consumed iron-rich foods. The odds of iron rich food consumption were high among children in the age group of 12-17 months (AOR = 4.81, 95% CI: 3.67, 6.31) and 18-23 months (AOR = 9.3, 95% CI: 6.55, 13.2), and who fed minimum acceptable diet (AOR = 22.5, 95% CI: 11.65, 43.46). Moreover, a child from a mother who had work (AOR = 1.49, 95% CI: 1.08, 2.06), and with a mother who had more than four ANC visits during her pregnancy of the most recent live birth (AOR = 1.87; 95%CI: 1.36-2.55) had higher odds of iron-rich food consumption compared to their counterparts. On the other hand, children who were breastfeeding (AOR = 0.72, 95% CI: 0.53, 0.97), and mothers aged 15-19 (AOR = 0.48, 95% CI: 0.27, 0.85) decreased the odds of iron rich food consumption. Conclusion Consumption of iron-rich food is low among children aged 6-23 months in Sierra Leone. Iron-rich food consumption among children was significantly associated with maternal occupation, child's age, child's breastfeeding status, taking drugs for intestinal parasites, minimum acceptable diet, frequency, and timing of ANC, and region. Thus, special emphasis should be given to those children aged between 6-11 months, currently breastfeeding, children who did not get the minimum acceptable diet, and children from women who did not have work.